Studies on soil organic carbon and some physico-chemical properties as affected by different land uses in Eritrea - NUGUSE, MAKDA TESFAY; SINGH, BALWAN; OGBAZGHI, WOLDESELASSIE (Journal of Soil and Water Conservation, 2019)
The study was conducted at Adi-jin, Dekigebru, Habrengka and Hamelmalo in Eritrea, Africa, to investigate the effect of different land uses (LU) on soil organic carbon (SOC) and physico-chemical properties of the soil. Stratified random sampling method was used to collect soil samples from three land uses (natural forest, cultivated and grazing lands). Soil samples were collected from two depths (0- 20 cm and 20-50 cm) using soil probe from all land uses and composite samples were prepared for analysis; separate samples were taken with core sampler from 0-20 cm soil depth for bulk density determination. The samples were analyzed for bulk density, texture, pH, electrical conductivity (EC), organic matter (OM), SOC, available nitrogen (N), phosphorus (P) and cation exchange capacity (CEC). The pH and EC ranged from moderately to strong alkaline, except forest in Adi-jin which was neutral and all were non-saline. Irrespective of the sites and depth, OM, SOC (%) and SOC stock were in order: forest > cultivated > grazing LUs. Within the forest LU, SOC percentage increased with increase in elevation, however in the remaining LUs the change in SOC percentage did not show any specific trend. Conversion of natural forest into grazing and cultivation caused 43.24% and 37.84% SOC loss, respectively. All the chemical properties showed significant difference among the sites except available N. OM, SOC and pH were significantly different among the LUs. SOC was found to be highly significantly and negatively correlated (p < 0.01) with pH, whereas positively with OM and available N. OM showed highly significant (p < 0.01) negative correlation with pH and positive with available nitrogen.